Collision-induced Mass Analyzed Ion Kinetic Energy (CID/MIKE) Spectra of Isobaric Ions - D. Stahl; J.C. Tabet (CHIMIA)
Collision-induced mass analyzed ion kinetic energy spectra of isobaric ions requiring a mass separation of 3500 prior to analysis of kinetic energy of fragments has been achieved on a VG-ZAB-2F mass spectrometer. Examples of spectra of a single ionic species obtained under these conditions are given.